Edu-game Application Based-Android Quantity and Unit Concepts Using Game Engine Constructs 2 - Nur Khoiri; Wahyu Adien Perdana; Wijayanto (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to produce alternative learning media about understanding the concept of unit size as an interactive and fun educational tool. This research uses the Research and Development (R&D) method and the product development model uses the MDLC (Multimedia Development Life Circle)) consisting of six stages, namely concept, design, material collecting, assembly, testing, distribution. The media expert validation test concluded that media expert 1 with an average percentage of 77% included the criteria of "Appropriate", media expert 2 with an average percentage of 80% included the criteria of "Very Eligible", and media expert 3 with an average percentage of 97% included criteria of "Very Eligible". The overall results of the validation of media experts obtained an average percentage of 84% including the "Very Eligible" criteria. Limited trials with 32 respondents resulted in an overall testing average of 97% including the criteria of "Very Eligible" and for achieving student learning outcomes an average of 84.34 was obtained including the criteria above the KKM. The results of this study are the Edugame Application of the Android-Based Concept of Units and Quantities Using Game Engine Construct 2 which is suitable for use.